1995
DOI: 10.1139/g95-049
|View full text |Cite
|
Sign up to set email alerts
|

DNA-strand breaks in chromosomes of early mouse embryos as detected by in situ nick translation and gap filling

Abstract: The nick translation and gap filling procedures, without external addition of nicking enzymes, were performed in situ on fixed chromosomes of mouse preimplantation and postimplantation embryos and of bone marrow in order to detect possible DNA single-strand breaks (nicks and (or) gaps). All chromosome preparations were made using the same technique. Nick translation of chromosomal DNA with DNA polymerase I (Pol I) or gap filling with the Klenow fragment of Pol I in the presence of biotinylated-dUTP, demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Analysis of these data together with the course of changes in SCE during early development (Bennett and Pedersen, 1984;Vogel and Spielmann, 1988;El-Hage and Singh, 1990) sug-gests that intense DNA nicking may underlie a higher SCE level during preimplantation compared to the later postimplantation stages. In support are the recent results of Patkin et al (1995), who have shown an increase in SSB level in 4-cell embryos and early blastocysts using in situ nick translation in the absence of exogenous nucleases. From the data it follows that there is a possible relationship between the increase in the SCE and SSB levels.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Analysis of these data together with the course of changes in SCE during early development (Bennett and Pedersen, 1984;Vogel and Spielmann, 1988;El-Hage and Singh, 1990) sug-gests that intense DNA nicking may underlie a higher SCE level during preimplantation compared to the later postimplantation stages. In support are the recent results of Patkin et al (1995), who have shown an increase in SSB level in 4-cell embryos and early blastocysts using in situ nick translation in the absence of exogenous nucleases. From the data it follows that there is a possible relationship between the increase in the SCE and SSB levels.…”
Section: Discussionsupporting
confidence: 83%
“…SSB in DNA may be of importance in the formation of two events occurring in the course of normal development: the high level of sister chromatid exchanges (SCE) in mouse embryos and recombination rate of human minisatellite DNA. There is ample evidence indicating that SCE level is 5 to 6-fold higher in embryos during the preimplantation stage than in the later developmental stages (Bennett and Pedersen, 1984;Elbing and Colot, 1987;Vogel and Spielmann, 1988;El-Hage and Singh, 1990;Patkin et al, 1995). It has been thought that high SCE level in early embryos is an attribute of undifferentiated cells (Vogel and Spielmann, 1988), which is related to DNA repair (Bennett and Pedersen, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Both interphase nuclei and metaphase chromosomes were labeled. Authors wrote that &&chromosomes appeared to be rather uniformly stained with prominent &&dots'' of different sizes and di!erent intensities of gray'' (Patkin et al, 1995). In our opinion, the label distribution in chromosomes is uneven and resembles G banding.…”
Section: Heterochromatin Formation Via Dna Breaksmentioning
confidence: 75%
“…Equal sensitivity of holoenzyme DNA polymerase I and its Klenow fragment means that the DNA breaks are single stranded. No labeling was observed in postimplantation embryo and in bone marrow cells (Patkin et al, 1994(Patkin et al, , 1995. Dramatically large scale of DNA nicking phenomenon was demonstrated by alkaline agarose gel microelectrophoresis of DNA from individual embryonic teratocarcinoma stem cell nuclei (Vatolin et al, 1997).…”
Section: Heterochromatin Formation Via Dna Breaksmentioning
confidence: 97%
See 1 more Smart Citation